2020
DOI: 10.46592/turkager.2020.v01i02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cassava Effluent as Organic Admixture in Concrete Production for Farm Structures

Abstract: This paper evaluated the influence of cassava effluent on the compressive strength of concrete for farm structures. Three sets of concrete cubes were produced with a concrete mix ratio of 1:2:4 (C 15) and a water to cement ratio (w c-1) of 0.5. The 1st set was produced with 100% fresh water (tap water). The 2nd set was produced with 75% partial replacement of the fresh water with fresh cassava effluent, while the 3rd set was produced with 75% partial replacement of the fresh water with old cassava effluent. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…At 1.5% corn starch concentration, the density generally increased by 6.3%, while at 2.0% corn starch concentration, the density generally increased by 7.8%. These findings are in conformity with earlier research findings by Akpokodje et al (2020) who reported that concrete produced with starch developed a higher (5% increment) density, compared to the normal concrete density. According to Suhad et al (2016), starch aids concrete compaction, thereby increasing its density in the process; and the compaction degree is a factor of the starch concentration introduced.…”
Section: Densitysupporting
confidence: 93%
See 1 more Smart Citation
“…At 1.5% corn starch concentration, the density generally increased by 6.3%, while at 2.0% corn starch concentration, the density generally increased by 7.8%. These findings are in conformity with earlier research findings by Akpokodje et al (2020) who reported that concrete produced with starch developed a higher (5% increment) density, compared to the normal concrete density. According to Suhad et al (2016), starch aids concrete compaction, thereby increasing its density in the process; and the compaction degree is a factor of the starch concentration introduced.…”
Section: Densitysupporting
confidence: 93%
“…According to Purnomo et al (2019), citric and hydrocyanic acids found in corn starch significantly affect the mechanical properties of concretes, a higher concentration of these acids tends to reduce the concrete's compressive strength. Additio-nally, Akpokodje et al (2020) in their research into the effect of cassava starch on concrete mechanical properties observed that, fresh cassava starch tends to produce concrete with higher compressive strength and density.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…There are basically two types of additives, namely the inorganic ones and organic (green) ones. Recently, organic additives are been favoured over inorganic (synthesized) ones due to the problems of climate change and other related issues (Akpokodje et al, 2021b). Organic additives and admixture, being natural materials tend to be environmentally friendly, and readily/cheaply available; though some of their engineering properties may be lower than those of their manufactured counterparts (Daramola et al, 2018;Umurhurhu and Uguru, 2019).…”
Section: Admixtures Usedmentioning
confidence: 99%
“…Concrete is a cement-based composite material that is widely utilized in civil engineering construction work, due to its high compressive strength, it's good thermal and radiation resistance, and it's durability, amongst other related factors (Kumbhar and Murnal, 2012;Akpokodje et al, 2020). Some parts of building structures that are largely utilize concrete include: foundation footings, floors, basement walls, columns, beams, slabs, etc.…”
Section: Introductionmentioning
confidence: 99%